Eksistensi Diri Anak Sd Di Era Digital: Integrasi Teori Hirarki Kebutuhan Maslow Dan Filsafat Eksistensial - Damayanti, Wahyuni; Iman, Muhamad Tamamul (LPPM Universitas Bina Bangsa, 2025)
This article aims to explore the existential self of elementary school children in the context of an increasingly digital world, through an integration of Abraham Maslow’s hierarchy of needs and existential philosophy. Amid the widespread influence of technology and social media in early childhood, children begin to show signs of seeking recognition, self-worth, and existential meaning—dimensions often overlooked in primary education. Employing a qualitative approach through library research, this study examines how the sequential fulfillment of basic human needs, as proposed by Maslow, contributes to the development of authentic character in children. Furthermore, insights from existential thinkers—particularly Karl Jaspers’ notions of freedom and authentic existence—are employed to deepen the understanding of self-awareness and existential responsibility in children today. The study finds that elementary school-aged children are already experiencing existential dynamics, such as the need for social validation, identity anxiety, and the search for meaning. These can be positively addressed through a holistic, humanistic, and reflective educational approach. The findings highlight the crucial role of teachers and curriculum design in creating a learning environment that addresses not only children's physical and cognitive needs, but also their existential and self-actualizing dimensions.